2018
DOI: 10.1016/j.bjm.2018.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoid production in sugarcane juice and synthetic media supplemented with nutrients by Rhodotorula rubra l02

Abstract: In order for the use of biological carotenoids to become feasible, it is necessary to have adequate low cost sources and improved methods of cultivation. The aim of this study was to evaluate the effect of supplementation with nitrogen, phosphorus, zinc, and magnesium, on the biomass and carotenoid volumetric production by yeast Rhodotorula rubra L02 using a complex medium (sugarcane juice) and synthetic media (sucrose and maltose) as substrates. The experimental design used for each substrate was randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Anthocyanins and carotenoids are color pigments that are randomly circulated in different sugarcane species. 23,28 The end product of the flavonoid biosynthesis pathway is anthocyanin. 40 The DFR gene encodes a key enzyme, named "dihydroflavonol-4-reductase", which causes the reduction of dihydroflavonols to leucoanthocyanidins in the proanthocyanidin and anthocyanin biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthocyanins and carotenoids are color pigments that are randomly circulated in different sugarcane species. 23,28 The end product of the flavonoid biosynthesis pathway is anthocyanin. 40 The DFR gene encodes a key enzyme, named "dihydroflavonol-4-reductase", which causes the reduction of dihydroflavonols to leucoanthocyanidins in the proanthocyanidin and anthocyanin biosynthesis pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds are widely distributed in living organisms having diverse roles in plant species. Among different phenolic compounds, flavonoids are prominent because they are biologically active in nature and have powerful antioxidant activities that protect plants against various abiotic and biotic stresses. , To date, few studies have found that the juice, leaves, and peels of S. officinarum contain flavonoid compounds whereas no detailed metabolic study has been conducted in other cultivated sugarcane species. ,,, Flavonoids and anthocyanins are used as synthetic additives and synthetic dyes, and the consumption of dietary flavonoids decreases the risk of cardio- and cerebrovascular diseases, cancer, diabetes, failing vision, and atherosclerosis. ,, Moreover, flavonoids have powerful antioxidant properties that protect the cellular organelles from oxidative damage and also protect from greater light stress. , Additionally, carotenoids (red, orange, and yellow organic pigments) and proanthocyanidins (key precursors of the red and blue-violet pigments) are also considered robust antioxidants that play a significant role in the protection of plant cells during oxidative stress. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to evaluate the effect of supplementation, Bonadio, Freita, and Mutton (2018) incubated yeast Rhodotorula rubra L02 in mediums with different concentrations of nitrogen, phosphorus, zinc and magnesium. The dry biomass and carotenoid yield were 2g/L and 0.003mg/L, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The others microorganisms pigment producer are the yeasts Rhodotorula sp., Rhodosporidium sp. for synthesis of torulen, torulahordin and β-carotene (Tkačova, 2015;Bonadio et al, 2018;). Many bacteria producing pigment are: Rhodococcus sp., Serratia sp., Rhodotorula sp.…”
Section: Introductionmentioning
confidence: 99%